Otopsi kejahatan bisnis - Sulaiman, Robintan, 1962- (Karawaci : Pusat Studi Hukum Bisnis, Fakultas Hukum, Universitas Pelita Harapan, 2001)
Issues on commercial crimes, Indonesia.
Includes bibliographical references (p. [335]).
Keywords: Commercial crimes -- Indonesia